PENGARUH PEMAHAMAN STANDAR AKUNTANSI PEMERINTAHAN DAN PEMANFAATAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Pada Organisasi Perangkat Daerah Kabupaten Tanjung Jabung Timur) - Novita Yanti (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
This study aims to analyze the effect of understanding government accounting standards and the use of accounting information systems on the quality of regional financial reports for the Tanjung Jabung Timur district government, this research was conducted on the technical agency and service in determining this sample using purposive sampling. The sample of this research is 84 financial management employees in each agency and service. Data was collected using a questionnaire instrument by giving a number of written questions to respondents and answered using a Likert scale. The technique used in this study was to test the validity of the reliability test, normality test, multicorrelation test, heteroscedasticity test, and hypothesis testing using multiple linear regression analysis (Multple Regression Analysis) using the SPSS 20.0 for Windows program. The results of this study indicate that the understanding of demand accounting standards and the utilization of the accounting system have a positive and significant impact on the quality of the financial statements of the Tanjung Jabung Timur district government.